A biomechanical study: Comparison of three different implant options in high Tibial osteotomy - Key, Sefa; Demir, Sukru; Aydin, Oguz; Say, Yakup; Erten, Mehmet (Elsevier Sci Ltd, 2022)
Background: Many implant options could be preferable for fixation after osteotomy in varus knee medial compartment arthrosis. Due to usage characteristics, it is important to compare the biomechanical properties of them. For this purpose, we aimed to examine three different implant types biomechanically in our study.Methods: Ovine tibiae undergoing medial open-wedge high tibial osteotomy were fixed in vitro with three different implants using an angular wedge plate, a metal block plate and an external fixator system. The fixed ovine tibiae were subjected to axial tensile, axial loading and three-point bending tests in a test machine. All biomechanical tests were repeated five times, the maximum and minimum values were ignored, and the average values of the remaining three test results were taken into account. The test results were interpreted after con-verted into force-elongation curves in Trapezium-X software. Findings: Biomechanical test results revealed some differences between implant types. While the metal block plate had the highest axial tensile strength value, it was the fixation group showing the lowest strength in axial load tests. The used fixator system was the highest strength in axial load tests and the lowest strength in axial tensile tests. Interpretation: Considering the clinically significant forces related to the biomechanical stability of the three different implants used for high tibial osteotomy, the fixator system would appear to be slightly superior, although it should be noted that torsional forces, as well as parameters that could change in living tissue, might affect the results.
Keywords: Proximaltibialosteotomy; Medialopen-wedgeosteotomy; varusknees; Biomechanics; Fixation